Konstruksi Makna Jurnalis Foto Kebencanaan dalam Karya Foto Jurnalistik - Bayu Anggara; Yadi Supriadi (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Journalists are one of the professions that demands a honesty and fairness for the culprit, because the journalist is as one the real form of information through media for a wide audience in the process of delivering messages through the mass media. Competent journalists must master the science of Communication in both the mass Communication, communication psychology, sociology of communication, philosophy, politics, social and cultural communication. The responsibility of a journalist should always be based on the truth and to be fought. A journalist under any circumstances is required to high the instinct and its sensitivity to the situation in the field as a photojournalist assigned to the disaster area. Photos is a medium with a strong image or visual message content to provide information for a wide audience so that every human being in the community can feel and know the reality that occurs in the field that Portrayed by a photo journalist. The purpose of this research is how the authors will examine how the construction of the meaning of a photojournalist in a solution in the disaster area with a qualitative method with a phenomenological approach using the theory of Alfred Schutz. The results of this study concluded that the construction of photojournalist in the Media Indonesia news papper is on the basis of social awareness of individual photo journalism by analyzing the situation and conditions in the field with Armed with experience and flying hours from each photo journalist in the program and become one of the living witnesses of the historical part of a natural disaster event that occurred by capture it through the camera lens as a medium of delivering the message to a wider audience. Abstrak. Wartawan adalah salah satu profesi yang menuntut sebuah kejujuran dan keadilan bagi para pelakunya, sebab wartawan adalah sebagai salah-satu bentuk nyata sebuah informasi melalui media bagi khalayak luas dalam proses penyampaian pesan melalui media massa. Wartawan yang berkompeten harus menguasai ilmu komunikasi. Tanggung jawab seorang wartawan harus selalu berpijak pada kebenaran dan harus diperjuangkan. Seorang wartawan dalam kondisi apapun dituntut untuk menjungjung tinggi insting dan kepekaannya terhadap situasi di lapangan salah satunya menjadi wartawan foto yang ditugaskan di daerah kebencanaan. Foto merupakan sebuah media dengan kandungan pesan gambar atau visual guna yang kuat untuk memberikan informasi bagi khalayak luas agar setiap insan manusia di lingkungan masyarakat dapat merasakan serta mengetahui realitas yang terjadi di lapangan yang digambarkan oleh seorang pewarta foto. Tujuan dari penelitian ini adalah bagaimana penulis akan meneliti bagaimana konstruksi makna seorang jurnalis foto dalam peliputannya di daerah kebencanaan dengan metode kualitatif dengan pendekatan fenomenologi menggunakan teori Alfred Schutz. Hasil penelitian ini menyimpulkan bahwa konstruksi jurnalis foto dalam peliputan foto kebencanaan di Harian Media Indonesia atas dasar kesadaran sosial dari masing-masing individu pewarta foto dengan menganalisis situasi dan kondisi di lapangan dengan berbekal pengalaman dan jam terbang dari setiap pewarta foto dalam peliputannya dan menjadi salah satu saksi hidup dari bagian sejarah sebuah peristiwa bencana alam yang terjadi dengan mengabadikannya melalui lensa kamera sebagai medium penyampaian pesan kepada khalayak luas.